The Influence of Audit Fees and Audit Rotation on Audit Quality in Chemical Sub-Sector Manufacturing Companies Listed on The Indonesia Stock Exchange - Maghfirah, Annesa Tasya; Jannah, Miftahul; Amiruddin, A.; Syamsuddin, S. (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of Audit Fees, Audit Rotation, and Audit Quality on the activeness of companies in conducting quality audits in chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research method used is quantitative with a logistic regression approach. Audit Fees are measured using the natural logarithm of professional fees, a dummy variable represents Audit Rotation, and Audit Quality is proxied by the auditor's Big Four status. The results show that all three independent variables positively and significantly affect company activity. The Nagelkerke R Square value of 0.923 indicates the model's high explanatory power. The model's goodness-of-fit test, with a Chi-Square value of 38.783 (p < 0.05), suggests that the model is suitable for use. Additionally, the classification accuracy reaches 100%, reinforcing the model's reliability in predicting the activeness category of companies.